Tie-Breaking Power in Committees - Alexander K. Wagner; Dura-Georg Granic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We investigate the effects of voting power in a committee in which one member (the chairman) holds, on top of a regular vote, also the power to break ties. The chairman is able to induce her preferred outcome much more often than predicted by theory, but only partially because of exercising tie-breaking power directly. The advantage of the chairman is largely determined by the limited strategic sophistication of committee members.
Keywords: C91; C92; D71; D72; 330